Chapter 3: Social networks and resilience in work teams - Pauksztat, Birgit (Edward Elgar Publishing, 2022)
This chapter explores social networks and resilience in an organizational context, focusing on work teams and their strategies for preparing, managing and learning from adversities. To date, only few studies have considered social networks in relation to the resilience of individuals and teams in organizations. This chapter shows how a social network perspective contributes to our understanding of team resilience. Specifically, it proposes that for research on team resilience, social networks can be relevant in three ways: they provide resources, they offer a way of analyzing responses to adversity, and they are important outcomes. Organizational design and interventions play a key role for resilience by influencing team members' networks, as well as the resources and strategies available to them. Future studies should take a holistic approach to explore team processes in response to adversities over time, taking into account the multilevel context in which teams are embedded.